Soil-cement for low cost roads - Megat Mohd Noor, Megat Johari; Abdul Aziz, Azlan (1988)
In ensuring rapid development to take place, provision of good roads is inevitable. The high cost of the conventional roads has not being served with graded latrite roads or none at all. Laterite road is notoripus for being dusty during the dry season., causing accumulation of undesiable blanket of dust on to house and vegitations. The dust may also have serious effect on health. Formation of deep ruts which are unpassable to vehicles at times is a common occurance in the wet seasons. Thus a high cost is incurred if the roads are to be maintained. The paper intends to present the works carried out at the University Pertanian Malaysia on the stabilization of lateritic soils using cement to act both as the road base and surfacing. The works include conducting basic soil mechanics tests on the soil-cement mixture and evaluating the effects of additives such as sand and rice husk ash on strength. A field trial on the construction of the soil-cement road was also done to evaluate the weathering effect under exposure.